Researching reinterpretations of educational activity in dialogic interactions during a fieldtrip. (March 2019) - Rajala, Antti; Akkerman, Sanne F.
Abstract: In this paper, we have conducted a detailed analysis of video-records of a class fieldtrip to an outdoor environmental education center to examine how the activity and its material context were interpreted, negotiated and sometimes contested in dialogic interactions between the students, teacher and two environmental educators. The findings shed light into the varied ways in which the different interpretations during the fieldtrip produced the forest and its surroundings as the material context of the activity. The findings also show how hybrid forms of activity were produced when the different interpretations collided and merged in the dialogic interactions among the actors. The study challenges existing ways of conceptualizing and researching school fieldtrips which to date have often disregarded the negotiation of diverse interpretations that participants make of the ongoing activity and its contexts. More generally, the study opens new ground for dialogical research approaches on learning and education by showing how an explicit focus on disjunctures between different interpretations of activity can shed light into the dynamics of the moment-to-moment production of emergent material contexts of activity.